Analisis Rasio Keuangan Organisasi Pengelola Zakat: Studi Kasus Kota/Kabupaten Di Indonesia - Shella Juniet Dubelta; Shopia Aulia Tasya; Sigit Trianto; Viki Anggrayani; Ersi Sisdianto (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
Financial ratio analysis is one of the measuring tools that can be used to analyze the financial condition of an institution. This study aims to measure and analyze the financial performance of City and District Zakat Management Organizations (OPZ) in Indonesia for the period 2019 and 2020 based on the ratio of activity, efficiency, amil funds, liquidity and growth. The method used in this research is descriptive qualitative with calculations using OPZ Financial Ratios published by PUSKAS BAZNAS. The data used in this study is secondary data obtained from financial reports published on the website. There are 8 samples used in 2019 and 10 samples used in 2020 that fulfill the sample criteria. The results of the study based on the overall activity ratio seen from the average performance in both years were effective and good. In the efficient ratio, 2019 as a whole showed inefficient results, while 2020 showed efficient results. The ratio of amil funds in both years showed good performance. The overall liquidity ratio in 2020 showed good performance results compared to 2019. The growth ratio in 2020 showed good performance, while 2019 showed poor performance.